Cloud-based service oriented architecture for social vehicular ad hoc network communications. (21st January 2020) - Arif, Muhammad; Wang, Guojun
This article offers a social networking platform for vehicles, based on cloud computing and service oriented architecture called CSS-IoV for communication and collaboration of vehicle to vehicle (V2V), and vehicle to infrastructure (V2I). CSS-IoV contains five layers: application layer, application service layer, services layer, cloud infrastructure layer, and layer of vehicles. The application layer operation is associated with the functionality of on-board units (OBUs) and road-side units (RSUs). The service layer runs on a service-oriented architecture (SOA) and cloud application services to improve applications. To expand and combine web services on this layer, the application developer and builders can effectively develop the new functions and programs for communication. With the support of dynamic and automated service collaboration, people can easily help and communicate with each other by using OBUs. Our results shows that the proposed scheme provide the best results in terms of both type of communication in VANETs.